2005
DOI: 10.1007/s00421-005-1341-4
|View full text |Cite
|
Sign up to set email alerts
|

High-intensity intermittent running training improves pulmonary function and alters exercise breathing pattern in children

Abstract: We investigated the effects of short duration running training on resting and exercise lung function in healthy prepubescent children. One trained group (TrG) (n = 9; three girls and six boys; age = 9.7 +/- 0.9 year) participated in 8 weeks of high-intensity intermittent running training and was compared to a control group (ContG) (n = 9; four girls and five boys; age = 10.3 +/- 0.7 year). Before and after the 8-week period, the children performed pulmonary function tests and an incremental exercise test on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 29 publications
2
52
2
7
Order By: Relevance
“…A year of intensive (12 h/week) swim training, for example, induced an increase in lung volumes (VC, TLC, and FRC) and expiratory flows (FEV 1 , MEF 50% , and MEF 25% ) in prepubescent girls compared with children who had a normal level of physical activity (109). Similarly, 8 weeks of twice-weekly high-intensity intermittent running training enhanced lung volume (FVC) and expiratory flows (FEV 1 , PEF, MEF 75% , and MEF 50% ) in prepubescent children compared with children who maintained their habitual physical activity (394).…”
Section: Physical Training Across the Lifespanmentioning
confidence: 93%
“…A year of intensive (12 h/week) swim training, for example, induced an increase in lung volumes (VC, TLC, and FRC) and expiratory flows (FEV 1 , MEF 50% , and MEF 25% ) in prepubescent girls compared with children who had a normal level of physical activity (109). Similarly, 8 weeks of twice-weekly high-intensity intermittent running training enhanced lung volume (FVC) and expiratory flows (FEV 1 , PEF, MEF 75% , and MEF 50% ) in prepubescent children compared with children who maintained their habitual physical activity (394).…”
Section: Physical Training Across the Lifespanmentioning
confidence: 93%
“…Potentially, HIT may be a useful alternative training approach. Children reach higher ventilations during high intensity exercise than adults, partially because they are more susceptible to developmental changes such as increased lung volumes, than adults depending upon the stage of maturation (Nourry et al, 2005). It is possible the adaptations could be even greater with children.…”
Section: Future Directionsmentioning
confidence: 99%
“…7 Nourrey C et al showed in a prospective study that aerobic exercise improves pulmonary function and alters exercise breathing pattern in children. 8 Fitch KD et al studied the effect of five months swimming training on school children with asthma and found improved lung function, and improved posture and fitness. 13 Kaufman C et al studied the effect of aerobic training on ventilatory efficiency in overweight children, and found that the training helped to reverse the decrements in cardiopulmonary function observed over a period of time in overweight children.…”
Section: Resultsmentioning
confidence: 99%
“…5 Most studies on the effects of physical activity are cross sectional ones, on special populations such as athletes or patients with COPD. [6][7][8] Physical activity rehabilitation is widely used in patients with pulmonary diseases. Exploration of the relation between aerobic exercise and respiratory functions, will aid in understanding the mechanisms of how aerobics improve patient's quality of life and in finding a better way to evaluate the effects of rehabilitation.…”
Section: Introductionmentioning
confidence: 99%